Definitions of the Notions of “Communicative Culture of Future Teachers of Preschool Education under the Conditions Master’s Degree Programs - Kharkivska, A. (Problems of Engineer-Pedagogical Education, 2019)
The essence of the definitions «culture», «communication», «communicative culture», «communicative culture of future teachers of preschool education» is considered in the article. On the basis of the study of scientific literature on this subject, the main approaches to the interpretation of the essence of these definitions are analyzed and their content is disclosed. A theoretical analysis of scientific works devoted to the communicative culture proves that in modern Ukraine the requirements of employers for graduates of higher pedagogical education institutions have significantly changed. A modern specialist should have a fairly high level of professional communication skills, which allows interacting effectively with other members of pedagogical communities and ensures the success of their professional activities and further professional growth. The author comes to the conclusion that communicative culture is one of the defining properties of a modern human being, since it occupies a leading place in the general cultural and professional development of the individual. Communicative culture fully includes essential personal characteristics (abilities, knowledge, skills, value orientations, attitudes, personality qualities) and is a prerequisite for successful self-realization of the individual, including the sphere of professional development. The teacher of preschool education constantly faces various issues of interpersonal communication.